Numerical code of Tuvan linguistic culture in proverbs (as contrasted to a number of Turkic and Mongolian languages of the peoples of Russia) - Bredis, Mikhail A.; Lomakina, Olga V.; Borisova, Anna S.; Lazareva, Olesya V. (The New Research of Tuva, 2022)
The article analyzes Tuvan paremias with the numerical component “one”, “two”, “three”, retrieved from various lexicographic sources by unselected sampling, and compares them with proverbs in the Khakas, Altai, Kumyk, Kalmyk and Buryat languages. In our work, we used the methods of historical and etymological, descriptive and analytical, linguistic and culturological analysis as well as the method of structural and semantic modeling. This made it possible to draw an interlanguage comparison of paremiological units in the aspect of comparative linguoaxiology and ethnolinguoculturology.It has been found out that the paremiological units of the Tuvan linguistic culture are mostly based on symbolic and sacred semantics of numbers. They feature popular beliefs, rituals, folklore and mythological images. The same is typical for the paremiological fund of languages considered alongside. It is noted that there is a significant number of common points in the symbolism of the numbers of the Turkic and Mongolian paremias. This is due to both the universal panhuman character of numerical symbolism and the kinship of these languages included in the Altai linguistic macrofamily. It can also be explained using the theory of cultural and linguistic transfer.
Keywords: cultural code; paremia; proverb; Tuvan language; Tuvan folklore; cultural transfer; symbolism of numbers; numerical component; numerical code